Isolation and Diagnosis of Parasites from Different Soils in Baghdad City - Al-Khamesi, Maisam Balasim (Al-Nahrain Journal of Science, 2018)
A study was conducted to determine the prevalence of parasites in soil texture (loam) by using four techniques (salt floatation, zinc sulphate floatation, sedimentation and filter paper technique). During the period from December 2012 to May 2013, 70 soil samples were collected and analyzed from six various sites of Baghdad City such as (house garden, vicinity of house, vicinity of gutter, waste dumps, vegetable farm and hospital garden like Alyarmouk teaching hospital and Central teaching hospital of pediatric). The prevalence of soil parasites was as follows: Toxocara spp. eggs isolated by two floatation techniques (salt and zinc floatation techniques), but this parasite appeared significant in its floatation by salt floatation technique (p= 0.042), while protozoan cysts appeared highly significant in zinc floatation technique (p= 0.00001). In addition, larvae of Strongloides stercoralis showed highly significance in sedimentation and filter paper technique (p=0.0001 and p= 0.001) respectively. Furtherly, female of Strongloides stercoralis appeared significant in its isolation in sedimentation (p= 0.0463), Ascaris lumbricoides (ova) showed highly significant in sedimentation technique (p= 0.0043). These results concluded that the Toxocara spp. eggs more prevelant than other parasites in soil samples, and the soil may play an important role in transmission of zoonotic parasite diseases to human. In addition, the control of high population of animals such as stray dogs and cats is necessary to reduce the distribution of parasites.